Lightning Surge Analysis for Overhead Lines Considering Corona Effect - Xiaoqing Zhang; Kejie Huang (Applied Sciences, 2021)
Corona discharge characteristics are measured in a corona cage. The difference is found between the q–u curves under double exponential and damped oscillation surges. The behavior of the minor loops is revealed for the q–u curves under positive and negative damped oscillation surges. An extended improvement is made on the traditional approach for modeling of the q–u curves under damped oscillation surges. The extended approach has the capability of describing the complicated trajectory feature of the minor loops. On the basis of the extended approach, an efficient method is proposed for performing lightning surge analysis of overhead lines considering the corona effect. In the proposed method, an overhead line with corona is divided into a certain number of line segments. Each segment is converted into a circuit unit consisting of a non-linear branch and a linear circuit. With these circuit units connected in sequence, a complete equivalent circuit is constructed for the overhead line with corona. The transient responses can be obtained from the solution to the equivalent circuit. Then, the calculated results are compared with the field test results on a test overhead line.